BIMBINGAN DAN KONSELING KARIR BAGI ANAK PENYANDANG DISABILITY - Ahmad Syarqawi (Universitas Islam Negeri Sumatera Utara Medan, 2018)
Careers are a very important part during human life. With a career, individuals can live prosperous, aiming, meaningful and so forth. The importance of a career in human life enables rulers in every country to give every individual the opportunity to make strategic moves in developing his career. Therefore, this simple writing will provide a series of thoughts and opinions of experts in discussing careers for children with disability.Keywords: Concerting career, disability